(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article delineates the dystopian realities and social alienation in Kazuo Ishiguro’s Never Let Me Go. The novel is set in a parallel world where human clones are fashioned for the only purpose of organ donation.